Pembuatan Briket Dari Produk Torefaksi Pelepah Sawit - Ramdhani Asywal; Zuchra Helwani; Warman Fatra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm frond is biomass that has not been widely used as a renewable energy source. Torrefaction is a pretreatment process to improve the quality of the biomass as solid fuel. The aims of this research was to made briquette from palm frond which appropriate with SNI, and then to determined the effects of particle size, pressure and filler composition on response toward calorific value and pressure using Responce Surface Methodology (RSM). Palm frond uses sieve 60, 80 and 100 mesh. Pressure 100, 110 and 120 kg/cm2, and tapioca adhesive composition 10, 20 and 30%-wt. The highest calorific value was 3989,05 cal/g which obtained at 100 mesh of particle size, pressure 120 kg/cm2, and filler compostion 10%-wt. The highest pressure was 8,92759 kg/cm2 which obtained at 100 mesh of particle size, pressure 120 kg/cm2 and filler composition 30%-wt. Process conditions is very influence significantly on the calorific value and compressive strength is the composition of the adhesive and the pressing pressure. Keywords : Briquette, Torrefaction, Responce Surface Methodology, Calorific Value, Renewable Energy